Perlecan: a review of its role in neurologic and musculoskeletal disease - Lavorgna, Tessa R.; Gressett, Timothy E.; Chastain, Wesley H.; Bix, Gregory J. (Frontiers in Physiology, 2023)
Perlecan is a 500 kDa proteoglycan residing in the extracellular matrix of endothelial basement membranes with five distinct protein domains and three heparan sulfate chains. The complex structure of perlecan and the interaction it has with its local environment accounts for its various cellular and tissue-related effects, to include cartilage, bone, neural and cardiac development, angiogenesis, and blood brain barrier stability. As perlecan is a key contributor to extracellular matrix health involved in many tissues and processes throughout the body, dysregulation of perlecan has the potential to contribute to various neurological and musculoskeletal diseases. Here we review key findings associated with perlecan dysregulation in the context of disease. This is a narrative review article examining perlecan’s role in diseases of neural and musucloskeletal pathology and its potential as a therapeutic index. Literature searches were conducted on the PubMed database, and were focused on perlecan’s impact in neurological disease, to include ischemic stroke, Alzheimer’s Disease (AD) and brain arteriovenous malformation (BAVM), as well as musculoskeletal pathology, including Dyssegmental Dysplasia Silverman-Handmaker type (DDSH), Schwartz-Jampel syndrome (SJS), sarcopenia, and osteoarthritis (OA). PRISMA guidelines were utilized in the search and final selection of articles.Increased perlecan levels were associated with sarcopenia, OA, and BAVM, while decreased perlecan was associated with DDSH, and SJS. We also examined the therapeutic potential of perlecan signaling in ischemic stroke, AD, and osteoarthritic animal models. Perlecan experimentally improved outcomes in such models of ischemic stroke and AD, and we found that it may be a promising component of future therapeutics for such pathology. In treating the pathophysiology of sarcopenia, OA, and BAVM, inhibiting the effect of perlecan may be beneficial. As perlecan binds to both α-5 integrin and VEGFR2 receptors, tissue specific inhibitors of these proteins warrant further study. In addition, analysis of experimental data revealed promising insight into the potential uses of perlecan domain V as a broad treatment for ischemic stroke and AD. As these diseases have limited therapeutic options, further study into perlecan or its derivatives and its potential to be used as novel therapeutic for these and other diseases should be seriously considered.